113 Benefit-risk of ofatumumab in treatment-naïve early relapsing multiple sclerosis patients. Issue 6 (27th May 2022) - Gärtner, Jutta; Hauser, Stephen; Bar-Or, Amit; Montalban, Xavier; Cohen, Jeffrey; Cross, Anne; Deiva, Kumaran; Häring, Dieter; Su, Wendy; ,
Abstract : Objective: To evaluate the benefit-risk profile of ofatumumab treatment in patients with early relapsing multiple sclerosis (RMS) subgroup in Phase 3 ASCLEPIOS I/II trials. Methods: Key efficacy and safety outcomes were assessed in the newly diagnosed, treatment-naïve subgroup who received ofatumumab or teriflunomide as first-line therapy in the trials (n=615, 32.7% of total patients). Results: Compared to patients on teriflunomide, ofatumumab reduced ARR by 50.3% (0.09 vs 0.18; p<0.001), 3mCDW risk by 38% (10.1% vs 12.8%; p=0.065), 6mCDW risk by 46% (5.9% vs 10.4%; p=0.044), gadolinium- enhancing T1 lesions/scan by 95.4% (0.02 vs 0.39: p<0.001), and new/enlarging T2 lesions/year by 82.0% (0.86 vs 4.78, p<0.001). Treatment-emergent adverse events (AEs) occurred in 84.7% ofatumumab vs 86.0% teriflunomide-treated patients; serious AEs were reported in 7.0% and 5.3%, respectively. Infection rates were comparable between ofatumumab (56.1%) and teriflunomide (56.5%); serious infection rates were 1.9% and 0.7%, respectively. 99.8% of injection reactions were mild-to-moderate; after the 4th injection, >70% RMS patients self-injected at home. Conclusion: Ofatumumab is the first anti-CD20 DMT that can be self-administered at home, as demonstrated in ASCLEPIOS. Here, ofatumumab showed superior efficacy vs teriflunomide with low absolute relapse rates, very low MRI lesion activity and prolonged time to disability worsening. Funding statement: This study was funded by Novartis Pharma AG, Basel, Switzerland. teresa.sawtell@novartis.com